2017
DOI: 10.1038/srep45190
|View full text |Cite
|
Sign up to set email alerts
|

Zinc deficiency and low enterocyte zinc transporter expression in human patients with autism related mutations in SHANK3

Abstract: Phelan McDermid Syndrome (PMDS) is a genetic disorder characterized by features of Autism spectrum disorders. Similar to reports of Zn deficiency in autistic children, we have previously reported high incidence of Zn deficiency in PMDS. However, the underlying mechanisms are currently not well understood. Here, using inductively coupled plasma mass-spectrometry to measure the concentration of Zinc (Zn) and Copper (Cu) in hair samples from individuals with PMDS with 22q13.3 deletion including SHANK3 (SH3 and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 66 publications
4
59
0
2
Order By: Relevance
“…Interestingly, all four have been implicated in studies of neuropsychiatric disorders. These genes were CNTN4, a cell adhesion molecule associated with autism [55] and schizophrenia [56]; PCDHGA10, a member of the protocadherin family of cell adhesion proteins which has been implicated in schizophrenia and autism [44]; SLC39A4, a zinc transport protein known to be regulated by SHANK3, a highly penetrant risk factor for autism [57]; and SORCS1, which alters amyloid precursor protein processing and is associated with Alzheimer's disease [58].…”
Section: Correlation and Overlap Analysismentioning
confidence: 99%
“…Interestingly, all four have been implicated in studies of neuropsychiatric disorders. These genes were CNTN4, a cell adhesion molecule associated with autism [55] and schizophrenia [56]; PCDHGA10, a member of the protocadherin family of cell adhesion proteins which has been implicated in schizophrenia and autism [44]; SLC39A4, a zinc transport protein known to be regulated by SHANK3, a highly penetrant risk factor for autism [57]; and SORCS1, which alters amyloid precursor protein processing and is associated with Alzheimer's disease [58].…”
Section: Correlation and Overlap Analysismentioning
confidence: 99%
“…This leads to synaptic defects and can also lead to autism [94,99]. Moreover, the relation of zinc uptake and the expression of Shank3 regarding autism has been studied recently [100]. This study only included participants with genetically confirmed diagnosis of Phelan McDermid Syndrome (PMDS) with deletion of Shank3 gene [100].…”
Section: Zinc Deficiencymentioning
confidence: 99%
“…Moreover, the relation of zinc uptake and the expression of Shank3 regarding autism has been studied recently [100]. This study only included participants with genetically confirmed diagnosis of Phelan McDermid Syndrome (PMDS) with deletion of Shank3 gene [100]. The study showed that low Shank3 levels resulted in abnormally low zinc transporter, which led to low zinc concentration [100].…”
Section: Zinc Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting evidence suggests that the released free zinc might contribute to the excitotoxicity of hippocampal neuronal injury aer brain trauma and that the accumulation of Zn 2+ might be part of the mechanism responsible for reduced neuronal survival following injury; however, this hypothesis has not been fully proven yet. 7,[10][11][12][13][14][15] Vesicular free zinc is the only form of zinc which is readily stained and which can be revealed by histochemical techniques with any certainty. 4 Direct histochemical detection of synaptic zinc is difficult and puts high demand on sample preparation and treatment and the small detectable amount of zinc in vesicles in the zinc-containing neurons is only a small fraction of the total zinc in the brain.…”
Section: Introductionmentioning
confidence: 99%